GAMBARAN DIMENSI INTERNAL DALAM KONSEP DIRI ANAK ASUH UPTD KAMPUNG ANAK NEGERI SURABAYA - Greisca Rosa Shafira; Oedojo Soedirham (Universitas Airlangga, 2017)
Every child has rights for survival, growth, development and protection from violence and discrimination. Family’s problem such as poverty, bad relationship between children and p arents, divorce, and acts of violence in children that affecting children become street children and abandoned children. Street children are very close to violence, neglected by parents, economic problems that result in children not attending school or an inadequate life. Although children in UPTD Kampung Anak Negeri has background as street children and abandoned children but with training that provided, the children are able to achieve a proud achievement. The research was conducted at UPTD Kampung Anak Negeri Surabaya with descriptive method of qualitative approach. The first variable in this research is the characteristics of children consisting of the background of p arenting, achievements, and activities that are occupied. The second variable is the internal dimension factor of s elf-concept consisting of selfidentity, self-behavior, and self-assessment. Instrument in this research is guidance of interview and observation with informant amounted to 8 people who already have achievements. Most children already know their self-identity. Most children are satisfied with their self if it compared with before they in UPTD Kampung Anak Negeri. Most children are already aware and responsible with the task they do. The conclusions of this study indicate that the self-concept supports the creation of good mental health.